Polbeng Business Expo Chapter II (Case Study on Kue Mak Ulfa and Es Jagung Lumer MSMEs) - Siti Norhaslinda; Nageeta Tara Rosa (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
Exhibitions serve as an effective medium for commercial communication by introducing products and services while strengthening relationships between businesses and consumers. In the digital era, integrating exhibitions with social media promotion has become an essential strategy for improving the competitiveness of Micro, Small, and Medium Enterprises (MSMEs). This project aims to implement social media as a promotional medium for Kue Mak Ulfa and Es Jagung Lumer MSMEs during their participation in the Polbeng Business Expo Chapter II in 2025. The project was conducted through several stages, namely preparation, implementation, accomplishment, and reporting. The preparation stage included selecting MSME tenants, conducting location surveys, and planning digital marketing activities. The implementation stage involved creating MSME business profiles, producing 30 promotional videos and 30 product catalogs, publishing promotional content on Instagram, Facebook, and WhatsApp for one month before the exhibition, creating QRIS payment systems, and preparing financial reports and financial ratio analyses. The results indicate that the integration of digital marketing and exhibition activities successfully enhanced the visibility of both MSMEs, strengthened brand awareness, and increased consumer purchasing interest. Furthermore, the promotional content enabled the businesses to reach a wider audience beyond the exhibition venue, while QRIS implementation simplified the payment process and improved customer convenience. Overall, this project demonstrates that consistent social media promotion combined with exhibition participation is an effective strategy for supporting MSME marketing performance and business development in the digital era.